Modeling of Particle Trajectory and Erosion of Large Rotor Blades. (21st February 2016) - Ghenaiet, Adel
Abstract : When operating in hostile environments, engines components are facing a serious problem of erosion, leading to a drastic drop in aerodynamic performance and life-cycle. This paper outlines the modeling and simulation of particle trajectory and erosion induced by sand particles. The governing equations of particle dynamics through the moving of large rotor blades are introduced and solved separately from the flow field by using our in-house particle tracking code based on the finite element method. As the locations of impacts are predicted, the erosion is assessed by semiempirical correlations in terms of impact conditions and particle and target surface characteristics. The results of these computations carried out for different concentrations of suspended dust (sand) cloud generated at takeoff conditions reveal the main areas of impacts with high rates of erosion seen over a large strip from the blade suction side, around the leading edge and the pressure side of blade. The assessment of the blade geometry deterioration reveals that the upper corner of blade suffers from an intense erosion wear.